Antifungal Hydrolases in Pea Tissue: II. Inhibition of Fungal Growth by Combinations of Chitinase and β-1,3-Glucanase - Mauch, Felix; Mauch-Mani, Brigitte; Boller, Thomas (My University, 1988)
Chitinase and ß-1,3-glucanase purified from pea pods acted synergistically in the degradation of fungal cell walls. The antifungal potential of the two enzymes was studied directly by adding protein preparations to paper discs placed on agar plates containing germinated fungal spores. Protein extracts from pea pods infected with Fusarium solani f.sp. phaseoli, which contained high activities of chitinase and ß-1,3-glucanase, inhibited growth of 15 out of 18 fungi tested. Protein extracts from uninfected pea pods, which contained low activities of chitinase and ß-1,3-glucanase, did not inhibit fungal growth. Purified chitinase and ß-1,3-glucanase, tested individually, did not inhibit growth of most of the test fungi. Only Trichoderma viride was inhibited by chitinase alone, and only Fusarium solani f.sp. pisi was inhibited by ß-1,3-glucanase alone. However, combinations of purified chitinase and ß-1,3-glucanase inhibited all fungi tested as effectively as crude protein extracts containing the same enzyme activities. The pea pathogen, Fusarium solani f.sp. pisi, and the nonpathogen of peas, Fusarium solani f.sp. phaseoli, were similarly strongly inhibited by chitinase and ß-1,3-glucanase, indicating that the differential pathogenicity of the two fungi is not due to differential sensitivity to the pea enzymes. Inhibition of fungal growth was caused by the lysis of the hyphal tips.